Enhancing Motor Development of Premature Infants: A Mobile App to Support Hospital-Home Intervention Program - Boude, Oscar; Ospina , Angélica; Pinto, Érika; Castellanos-Garrido, Adriana Lucía; Sandoval-Cuéllar, Carolina (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The integration of mobile devices into different sectors of society is an increasingly commonprocess; however, their integration as part of medical monitoring for treatments carriedout at home is still new, especially their application to the motor development of prematurechildren. This work determines the elements that a mobile application must have to supporta hospital-home intervention program aimed at improving motor development in prematureinfants. The application is designed to work in Android and iOS platforms for mobile devicesand to support the hospital-home strategy developed at the Universidad de La Sabana. In thisstudy, an evolutionary device was created, developed and validated along with its Unity3D tool. The result is an intuitive application that allows parents to strengthen the motor developmentof their children through a series of 10 exercises designed to stimulate the baby. Itconsists of a registry of babies, fundamentals, exercise modules and follow-up procedures.The conclusions indicate that although the application is intuitive, some parents have difficultyaccessing a mobile device, so it is necessary to create a web version of the application.